Cyanobacterial Soil Surface Consortia Mediate N Cycle Processes in Agroecosystems - Peng, Xin; Bruns, Mary Ann (Frontiers in Environmental Science, 2019)
Naturally occurring cyanobacterial growth on soil surfaces with udic moisture regimes has received far less study than biological soil crusts (BSCs) of xeric or aridic biomes. Because they are ephemeral and recurrent on udic soils, we refer to such cyanobacterial biofilms as soil surface consortia (SSCs) to distinguish them from classical BSCs. We assessed the ability of SSCs to fix N2 as well as take up NO3−-N in fertilized soils by testing a cyanobacterial enrichment from a local agricultural field. The metagenome of this consortium, designated DG1, consisted of Cylindrospermum sp. (90%) and genomes of six non-photosynthetic bacteria. We evaluated N2 fixation by DG1 in the presence of inorganic N by measuring biomass uptake of 15N2 during 7-days incubations in a controlled-atmosphere chamber in media containing 0, 62, 124, or 247 mg L−1NO3−-N. After 7 days, mean 15N atom % excess in DG1 biomass was 0.0143, 0.0029, 0.0037, and 0.0038 at the four NO3−-N concentrations, respectively. Mean 15N atom % excess in dead cell controls was not significantly larger than zero. Mean N2 fixation rates of 101.3, 18.9, 25.6, and 26.6 μg N g−1 dry biomass d−1, respectively, indicated that DG1 continued to fix N2 in the presence of NO3−-N, but at rates 4- to 5-fold lower than in N-free medium. We also assessed the potential for the SSC to retain soil NO3−-N by applying simulated rainfall to soil microcosms inoculated with three levels of DG1 grown for 1, 3, and 7 days at varied NO3−-N concentrations. Overall, inoculation resulted in 50–70% more soil N retained after rainfall (p < 0.001) compared to non-inoculated microcosms. The effect of establishment time was significant (p = 0.043). Since water infiltration rates through microcosms were not significantly affected, we inferred that SSC biomass absorbed and/or immobilized NO3−-N. These results show how SSCs can modulate soil N, either by fixing more N2 under N-limited conditions or by immobilizing inorganic N when concentrations are higher. Thus, naturally occurring or intentionally inoculated SSCs represent potential renewable sources of biologically fixed N and means for soil stabilization and N retention in diverse agricultural systems.